Evaluation of ancestral membership proportions and genotype distribution in the perception of Umami taste in Ecuadorian mestizos. (December 2017) - Paz-y-Miño, C.; García-Cárdenas, J.M.; López-Cortés, A.; Cabrera-Andrade, A.; Guevara-Ramírez, P.; González, D.A.; Zambrano, A.K.; Leone, P.E.
Abstract: Genetic variation to flavor perception contributes the population differentiation, where the T allele of SNP rs307377 of TAS1R3 gene influences the levels of appreciation of monosodium glutamate (MSG), for Umami taste. The aim of this study was to evaluate the distribution of polymorphism in the perception of Umami taste, and correlate to the ancestral proportions in the mestizo Ecuadorian population. The majority of participants presented C/C genotype. The ancestry was predominantly Native American.